GREEN SUPPLY CHAIN TRANSFORMATION IN MINING SERVICES: A HYBRID CONCEPTUAL EMPIRICAL STUDY OF BATTERY ELECTRIC MINING DUMP TRUCK ADOPTION IN INDONESIA - Denia, Rikko (ITB AAS Indonesia Surakarta, 2025)
The mining services industry in Indonesia is under growing pressure to adopt more sustainable operational practices in response to shifting environmental expectations, tightening regulatory demands, and evolving client requirements. Diesel powered haulage systems remain the dominant contributor to greenhouse gas emissions and cost inefficiencies within the mining supply chain. This study investigates how Battery Electric Mining Dump Trucks (BEMDT) can serve as a catalyst for green supply chain transformation in large-scale coal mining operations. Drawing on a qualitative case study approach supported by the Triple Bottom Line framework, the research incorporates operational observations and relevant literature to examine the feasibility, benefits, and barriers associated with BEMDT adoption. The findings reveal that electrifying haulage operations offers substantial environmental benefits through reduced emissions, alongside long-term economic gains driven by lower energy and maintenance costs. The transition also enhances alignment with the sustainability commitments of mining principals pursuing Net Zero pathways. However, challenges persist, particularly related to capital requirements, charging infrastructure, workforce readiness, and policy uncertainty. The study proposes a conceptual model that integrates electrification within the broader Green Supply Chain Management framework. The model provides both theoretical contributions and practical guidance for mining contractors seeking to enhance sustainability performance in emerging market contexts. Keywords: Battery Electric Mining Trucks, Green Supply Chain Management, Sustainable Operation, Triple Bottom Line, Indonesia.